Domestic abuse in later life: a secondary analysis of the Crime Survey for England and Wales - Bows, Hannah (European journal of criminology, 2025)
Until recently, older victims – and perpetrators – of domestic abuse were largely absent from both research and policy, leaving a lacuna of empirical and theoretical understandings of abuse in later life. This article presents the findings from the first study to use Crime Survey for England and Wales data on older adults to explore prevalence and risk factors for domestic abuse against adults aged 60–74 years old and, separately, adults aged 16–59 years. We find that risk factors for abuse are similar across the life course. In particular, socio-economic disadvantage, poor health and disability, and victim sex are constant correlates for victimisation, regardless of age. However, there are some important differences in the risk factors for partner and non-partner abuse in later life. Consistent with previous research involving all ages, we found that women were significantly more likely to be victimised by a partner than men (almost three times more likely in our study). However, when looking at abuse by non-partner family members, there was no statistically significant difference between the risk of victimisation for men and women. In other words, partner abuse disproportionately affects older women, but men and women are equally at risk of non-partner abuse. We propose that a move towards life course theories for understanding domestic abuse is required.